A legacy of learning : essays in honor of Jacob Neusner - Neusner, Jacob, 1932-; Avery-Peck, Alan J. 1953- (The Brill Reference Library of Judaism, 2014)
In a career spanning over fifty years, the questions Jacob Neusner has asked and the critical methodologies he has developed have shaped the way scholars have come to approach the rabbinic literature as well as the diverse manifestations of Judaism from rabbinic times until the present. The essays collected here honor that legacy, illustrating an influence that is so pervasive that scholars today who engage in the critical study of Judaism and the history of religions more generally work in a laboratory that Professor Neusner created. Addressing topics in ancient and Rabbinic Judaism, the Judaic context of early Christianity, American Judaism, World Religions, and the academic study of the humanities, these essays demarcate the current state of Judaic and religious studies in the academy today.